Optimization of Biodiesel Production from Sunflower Oil Using Sodalite-Based Catalyst via Taguchi Method - Hamid, Abdul; Jakfar, Amin; Rahmawati, Zeni; Armansyah, Muhammad Doni; Wahyuni, Tri; Purbaningtias, Tri Esti; Febriana, Ike Dayi; Abdullah, Mohammad; Ilmah, Aurista Miftahatul; Rohmah, Faizatur (Politeknik Negeri Malang, 2025)
The growing demand for alternative fuels has highlighted biodiesel as sustainable substitute for fossil diesel. In this study, biodiesel was produced from sunflower seed oil using heterogeneous catalyst synthesized from natural kaolin into sodalite via hydrothermal process. The synthesized catalyst was characterized using XRD, FTIR and SEM-EDS, confirming the transformation of kaolinite to sodalite. The transesterification reaction was conducted under varying methanol-to-oil molar ratios (1:12, 1:18, and 1:24) and temperatures (60, 65, and 70°C). A Taguchi orthogonal array (L9) was employed to statistically evaluate the effects of these parameters on methyl ester yield. Experimental results showed that both methanol ratio and reaction temperature significantly influenced biodiesel yield, with the highest yield of 90.44% obtained at 70°C and 1:18 molar ratio. Signal-to-noise ratio and ANOVA analysis indicated that the methanol-to-oil ratio was the most dominant factor (46.05%) compared to temperature (40.55%). The resulting biodiesel exhibited a flash point of 158°C, acid value of 0.06 mg-KOH/g, and iodine value of 84.06 g-I₂/100g, satisfying most ASTM D6751 and SNI 7182:2015 standards, though viscosity and density exceeded standard limits. Emission testing showed 16% reduction in CO emissions with increasing biodiesel blends, while NO and NOx emissions slightly increased.